Diagnostic Performance of Simultaneous [(18)F]-FDG PET/MR for Assessing Endoscopically Active Inflammation in Patients with Ulcerative Colitis: A Prospective Study - Langhorst, Jost (J Clin Med, 2020)
Background: To investigate the diagnostic performance of simultaneous (18)F-fluoro-deoxyglucose ([(18)F]-FDG) PET/MR enterography in assessing and grading endoscopically active inflammation in patients with ulcerative colitis. Methods: 50 patients underwent PET/MR 24 h before ileocolonoscopy. Inflammatory activities of bowel segments were evaluated with both Mayo endoscopic subscore and Nancy histologic index. MR, DWI (Diffusion-weighted imaging) and PET were utilized as qualitative parameters for detecting endoscopically active inflammation. SUVmaxQuot in each segment (maximum of standard uptake value relative to liver) was calculated to quantify inflammation. Results: In the study arm without bowel purgation, combined reading of PET and MR resulted in significantly increased specificity against each submodality alone (0.944 vs. 0.82 for MR and 0.843 for PET, p < 0.05) and highest overall accuracy. In the study arm with bowel purgation, the significantly lower specificity of PET (0.595) could be markedly improved by a combined reading of PET and MR. Metabolic conditions in bowel segments with both endoscopic and histological remission were significantly lower than in segments with endoscopic remission but persistent microscopic inflammation (SUVmaxQuot 0.719 vs. 0.947, p < 0.001). SUVmaxQuot correlated highly with Mayo endoscopic subscore (ρ = 0.718 and 0.606) and enabled grading of inflammatory activity. Conclusions: Simultaneous [(18)F]-FDG PET/MR may be considered as an alternative to endoscopy in clinical trials.